Chap 02 Real Analysis: Sequences and Series
Chap 02 Real Analysis: Sequences and Series
Chap 02 Real Analysis: Sequences and Series
Sequence
A sequence is a function whose domain of definition is the set of natural
numbers.
Or it can also be defined as an ordered set.
Notation:
An infinite sequence is denoted as
∞
{S n } or {Sn : n ∈ ¥} or {S1, S2 , S3 ,...........} or simply as {Sn }
n=1
Subsequence
It is a sequence whose terms are contained in given sequence.
∞ ∞
A subsequence of {S n } is usually written as {S nk } .
n=1
Increasing Sequence
A sequence {Sn } is said to be an increasing sequence if S n +1 ≥ S n ∀ n ≥ 1 .
Decreasing Sequence
A sequence {Sn } is said to be an decreasing sequence if S n +1 ≤ S n ∀ n ≥ 1 .
Monotonic Sequence
A sequence {Sn } is said to be monotonic sequence if it is either increasing or
decreasing.
S
{Sn } is monotonically increasing if Sn+1 − Sn ≥ 0 or n+1 ≥ 1, ∀ n ≥ 1
Sn
S
{Sn } is monotonically decreasing if Sn − Sn+1 ≥ 0 or n ≥ 1, ∀ n ≥ 1
S n+1
Strictly Increasing or Decreasing
{Sn } is called strictly increasing or decreasing according as
S n+1 > S n or S n+1 < S n ∀ n ≥ 1 .
Bernoulli’s Inequality
Let p ∈ ¡ , p ≥ −1 and p ≠ 0 then for n ≥ 2 we have
(1 + p ) > 1 + np
n
Proof:
We shall use mathematical induction to prove this inequality.
If n = 2
L.H.S = (1 + p) 2 = 1 + 2 p + p 2
R.H.S = 1 + 2 p
⇒ L.H .S > R.H .S
Sequences and Series -2-
(1 + p ) = (1 + p )(1 + p )
k +1 k
Now
> (1 + p )(1 + kp ) using (i)
= 1 + kp + p + kp 2
= 1 + (k + 1) p + kp 2
≥ 1 + (k + 1) p ignoring kp 2 ≥ 0
⇒ (1 + p ) > 1 + ( k + 1) p
k +1
Since the truth for n = k implies the truth for n = k + 1 therefore condition II of
mathematical induction is satisfied. Hence we conclude that (1 + p ) > 1 + np .
n
Example
n
1
Let S n = 1 + where n ≥ 1
n
−1
To prove that this sequence is an increasing sequence, we use p = , n ≥ 2 in
n2
Bernoulli’s inequality to have
n
1 n
1 − 2 > 1 − 2
n n
n
1 1 1
⇒ 1 − 1 + > 1 −
n n n
1− n 1− n n−1 n −1
n −1
n
1 1 n 1
⇒ 1 + > 1 − = = = 1 +
n n n n −1 n −1
⇒ Sn > S n −1 ∀ n ≥1
which shows that {Sn } is increasing sequence.
Example
n+1
1
Let tn = 1 + ; n ≥1
n
then the sequence is decreasing sequence.
1
We use p = 2 in Bernoulli’s inequality.
n −1
n
1 n
1 + 2 >1+ 2 ……….. (i)
n −1 n −1
where
1 n2 n n
1+ 2 = 2 =
n − 1 n − 1 n − 1 n + 1
1 n + 1 n
⇒ 1 + 2 = …………… (ii)
n − 1 n n − 1
n n
1 n
Now tn−1 = 1 + =
n − 1 n −1
n
1 n + 1
= 1 + 2 from (ii)
n − 1 n
Sequences and Series -3-
1 n +1
n n
= 1 + 2
n −1 n
n n + 1
n
> 1 + 2 from (i)
n − 1 n
1 n + 1
n
n n 1
> 1 + Q 2 > 2=
n n n −1 n n
n+1
n +1
= = tn
n
i.e. tn−1 > t n
Hence the given sequence is decreasing sequence.
Bounded Sequence
A sequence {Sn } is said to be bounded if there exists a positive real number λ
such that Sn < λ ∀ n ∈ ¥
If S and s are the supremum and infimum of elements forming the bounded
sequence {Sn } we write S = sup S n and s = inf S n
All the elements of the sequence S n such that Sn < λ ∀ n ∈ ¥ lie with in the
strip { y : − λ < y < λ} . But the elements of the unbounded sequence can not be
contained in any strip of a finite width.
Examples
(−1)n
(i) {U n} = is a bounded sequence
n
(ii) {Vn } = {sin nx} is also bounded sequence. Its supremum is 1 and infimum is −1 .
(iii) The geometric sequence {ar n −1} , r > 1 is an unbounded above sequence. It is
bounded below by a.
nπ
(iv) tan is an unbounded sequence.
2
Convergence of the Sequence
A sequence {Sn } of real numbers is said to convergent to limit ‘s’ as n → ∞ , if
for every positive real number ε > 0 , however small, there exists a positive integer n0 ,
depending uponε , such that Sn − s < ε ∀ n > n0 .
Theorem
A convergent sequence of real number has one and only one limit (i.e. Limit of
the sequence is unique.)
Proof:
Suppose {Sn } converges to two limits s and t, where s ≠ t .
s−t
Put ε = then there exits two positive integers n1 and n2 such that
2
Sn − s < ε ∀ n > n1
and Sn − t < ε ∀ n > n2
⇒ Sn − s < ε and Sn − t < ε hold simultaneously ∀ n > max(n1 , n2 ) .
Thus for all n > max(n1 , n2 ) we have
s − t = s − S n + Sn − t
Sequences and Series -4-
≤ Sn − s + S n − t
< ε + ε = 2ε
s−t
⇒ s − t < 2
2
⇒ s −t < s −t
Which is impossible, therefore the limit of the sequence is unique.
Note: If {Sn } converges to s then all of its infinite subsequence converge to s.
Cauchy Sequence
A sequence { xn } of real number is said to be a Cauchy sequence if for given
positive real number ε , ∃ a positive integer n0 (ε ) such that
xn − xm < ε ∀ m, n > n0
Theorem
A Cauchy sequence of real numbers is bounded.
Proof
Let {Sn } be a Cauchy sequence.
Take ε = 1 , then there exits a positive integers n0 such that
Sn − Sm < 1 ∀ m, n > n0 .
Fix m = n0 + 1 then
Sn = S n − S n0 +1 + S n0 +1
≤ S n − S n0 +1 + S n0 +1
< 1 + S n0 +1 ∀ n > n0
<λ ∀ n > 1 , and λ = 1 + S n0 +1 ( n0 changes as ε changes)
Hence we conclude that {Sn } is a Cauchy sequence, which is bounded one.
Note:
(i) Convergent sequence is bounded.
(ii) The converse of the above theorem does not hold.
i.e. every bounded sequence is not Cauchy.
Consider the sequence {Sn } where Sn = (−1)n , n ≥ 1 . It is bounded sequence because
(−1) n = 1 < 2 ∀ n ≥1
But it is not a Cauchy sequence if it is then for ε = 1 we should be able to find a
positive integer n0 such that Sn − Sm < 1 for all m, n > n0
But with m = 2k + 1 , n = 2k + 2 when 2 k + 1 > n0 , we arrive at
Sn − S m = (−1)2 n+2 − (−1) 2 k +1
= 1 + 1 = 2 < 1 is absurd.
Hence {Sn } is not a Cauchy sequence. Also this sequence is not a convergent
sequence. (it is an oscillatory sequence)
……………………………
Sequences and Series -5-
Divergent Sequence
A {Sn } is said to be divergent if it is not convergent or it is unbounded.
e.g. { n } is divergent, it is unbounded.
2
Note: If two subsequence of a sequence converges to two different limits then the
sequence itself is a divergent.
Theorem
If S n < U n < t n ∀ n ≥ n0 and if both the {Sn } and {tn } converge to same limits as
s, then the sequence {U n } also converges to s.
Proof
Since the sequence {Sn } and {tn } converge to the same limit s, therefore, for
given ε > 0 there exists two positive integers n1 , n2 > n0 such that
Sn − s < ε ∀ n > n1
tn − s < ε ∀ n > n2
i.e. s − ε < S n < s + ε ∀ n > n1
s − ε < tn < s + ε ∀ n > n2
Since we have given
Sn < U n < tn ∀ n > n0
∴ s − ε < Sn < U n < tn < s + ε ∀ n > max(n0 , n1 , n2 )
⇒ s − ε < Un < s + ε ∀ n > max(n0 , n1 , n2 )
i.e. Un − s < ε ∀ n > max(n0 , n1 , n2 )
i.e. lim U n = s
n→∞
Example
1
Show that lim n = 1 n
n→∞
Solution
Using Bernoulli’s Inequality
n
1 n
1 + ≥1+ ≥ n ≥1 ∀ n.
n n
Also
2
1 1
2 n
( n)
n 2 1
+ = + > > n ≥1
n n
1 1
n n
2
1
1
⇒ 1 ≤ n < 1 +
n
n
2
1
1
⇒ lim1 ≤ lim n < lim 1 +
n
n→∞ n→∞ n→∞
n
1
⇒ 1 ≤ lim n < 1 n
n→∞
1
i.e. lim n = 1 . n
n→∞
……………………..
Sequences and Series -6-
Example
1 1 1
Show that lim + + ............ + =0
n→∞ ( n + 1)
2
(n + 2) 2
(2 n)2
Solution
We have
1 1 1
Sn = + + ............ +
(n + 1) (n + 2)2
2
(2n) 2
and
n n
< S n <
(2n) 2 n2
1 1
⇒ < Sn <
4n n
1 1
⇒ lim < lim S n < lim
n→∞ 4n n→∞ n→∞ n
Theorem
If the sequence {Sn } converges to s then ∃ a positive integer n
1
such that Sn > s .
2
Proof
1
We fix ε = s > 0
2
⇒ ∃ a positive integer n1 such that
Sn − s < ε for n > n1
1
⇒ Sn − s < s
2
Now
1 1
s = s − s
2 2
< s − Sn − s ≤ s + ( S n − s )
1
⇒ s < Sn
2
Theorem
Let a and b be fixed real numbers if {Sn } and {tn } converge to s and t
respectively, then
(i) {aSn + btn } converges to as + bt.
(ii) {Sn tn } converges to st.
S s
(iii) n converges to , provided tn ≠ 0 ∀ n and t ≠ 0 .
tn t
Proof
Since {Sn } and {tn } converge to s and t respectively,
∴ Sn − s < ε ∀ n > n1 ∈ ¥
Sequences and Series -7-
tn − t < ε ∀ n > n2 ∈ ¥
Also ∃ λ > 0 such that Sn < λ ∀ n > 1 ( Q {Sn } is bounded )
(i) We have
( aSn + btn ) − ( as + bt ) = a ( Sn − s ) + b ( tn − t )
≤ a ( S n − s ) + b ( tn − t )
< a ε+ bε ∀ n > max (n1 , n2 )
= ε1 Where ε1 = a ε + b ε a certain number.
This implies {aSn + btn } converges to as + bt.
(ii) Sn tn − st = Sn tn − Sn t + Sn t − s t
= S n ( tn − t ) + t ( S n − s ) ≤ S n ⋅ ( tn − t ) + t ⋅ ( S n − s )
< λε + t ε ∀ n > max (n1 , n2 )
= ε2 where ε 2 = λ ε + t ε a certain number.
This implies {Sn tn } converges to st.
1 1 t − tn
(iii) − =
tn t tn t
tn − t ε 1
= < 1 ∀ n > max (n1 , n2 ) Q tn > t
tn t 2 t t 2
ε ε
= = ε3 where ε 3 = a certain number.
1 t 2 1 t
2
2 2
1 1
This implies converges to .
tn t
S 1 1 s
Hence n = Sn ⋅ converges to s ⋅ = . ( from (ii) )
tn tn t t
Theorem
For each irrational number x, there exists a sequence {rn } of distinct rational
numbers such that lim rn = x .
n→∞
Proof
Since x and x + 1 are two different real numbers
Q ∃ a rational number r1 such that
x < r1 < x + 1
Similarly ∃ a rational number r2 ≠ r1 such that
1
x < r2 < min r1 , x + < x + 1
2
Continuing in this manner we have
1
x < r3 < min r2 , x + < x + 1
3
1
x < r4 < min r3 , x + < x + 1
4
……………………………..........
……………………………..........
……………………………..........
1
x < rn < min rn−1 , x + < x + 1
n
Sequences and Series -8-
This implies that ∃ a sequence {rn } of the distinct rational number such that
1 1
x − < x < rn < x +
n n
Since
1 1
lim x − = lim x + = x
n→∞
n n→∞ n
Therefore
lim rn = x
n→∞
Theorem
Let a sequence {Sn } be a bounded sequence.
(i) If {Sn } is monotonically increasing then it converges to its supremum.
(ii) If {Sn } is monotonically decreasing then it converges to its infimum.
Proof
Let S = sup S n and s = inf S n
Take ε > 0
(i) Since S = sup S n
∴ ∃ Sn0 such that S − ε < Sn0
Since {Sn } is ↑ ( ↑ stands for monotonically increasing )
∴ S − ε < Sn0 < Sn < S < S + ε for n > n0
⇒ S − ε < Sn < S + ε for n > n0
⇒ Sn − S < ε for n > n0
⇒ lim S n = S
n→∞
(ii) Since s = inf S n
∴ ∃ Sn1 such that Sn1 < s + ε
Since {Sn } is ↓ . ( ↓ stands for monotonically decreasing )
∴ s − ε < s < Sn < Sn1 < s + ε for n > n1
⇒ s − ε < Sn < s + ε for n > n1
⇒ Sn − s < ε for n > n1
Thus lim S n = s
n→∞
Note
A monotonic sequence can not oscillate infinitely.
Example:
1 n
Consider {S n } = 1 +
n
As shown earlier it is an increasing sequence
2n
1
Take S 2 n = 1 +
2n
n
1
Then S 2 n = 1 +
2n
n n
1 2n 1 1
⇒ = ⇒ = 1 −
S 2 n 2n + 1 S 2 n 2n + 1
Using Bernoulli’s Inequality we have
Sequences and Series -9-
n
Q 1 −
1 n n 1 1 n
⇒ ≥ 1− > 1− = ≥ 1−
S2 n 2n + 1 2n 2 2n + 1 2n + 1
1
⇒ lim 2 − = lim tn
n→∞ t n n→∞
1 2t − 1
⇒ 2− =t ⇒ =t ⇒ 2t − 1 = t 2 ⇒ t 2 − 2t + 1 = 0
t t
⇒ ( t − 1) = 0 ⇒ t =1
2
Example
Let {Sn } be defined by S n +1 = S n + b ; n ≥ 1 and S1 = a > b .
It is clear that S n > 0 ∀ n ≥ 1 and S 2 > S1 and
Sn2+1 − Sn2 = ( Sn + b ) − ( Sn−1 + b )
= S n − S n−1
⇒ ( Sn+1 + Sn )( Sn +1 − Sn ) = Sn − Sn−1
S − S n −1
⇒ S n+1 − Sn = n
S n+1 + S n
Since S n +1 + S n > 0 ∀ n ≥ 1
Therefore S n +1 − S n and S n − S n−1 have the same sign.
i.e. S n+1 > S n if and only if S n > S n−1 and
S n+1 < S n if and only if S n < S n−1 .
Sequences and Series - 10 -
⇒ s = s+b2
⇒ s2 − s − b = 0
1 + 1 + 4b
Which shows that α = is the limit of the sequence.
2
Theorem
Every Cauchy sequence of real numbers has a convergent subsequence.
Proof
Suppose {Sn } is a Cauchy sequence.
Let ε > 0 then ∃ a positive integer n0 ≥ 1 such that
ε
Snk − Snk −1 < k ∀ nk , nk −1 , k = 1,2,3,.........
2
Put ( ) ( ) (
bk = S n1 − S n0 + S n2 − S n1 + ............ + S nk − S nk −1 )
⇒ bk = (S n1 − S n0 ) + ( S − S ) + ............ + ( S − S )
n2 n1 nk nk −1
≤ (S n1 − S n0 ) + ( S − S ) + ............ + ( S − S )
n2 n1 nk nk −1
ε ε ε
< + 2 + ............ + k
2 2 2
1 1 1 1 1 − 1k
= ε + 2 + ............ + k = ε
2 2 ( ) = ε 1 − 1
2 2 2 1− 2 1 2k
⇒ bk < ε ∀ k ≥1
⇒ {bk } is convergent
Q bk = Snk − Sn0 ∴ Snk = bk + Sn0
Where Sn0 is a certain fix number therefore S nk { } which is a subsequence of {S } is
n
convergent.
Sequences and Series - 11 -
Example
Let {Sn } be define by 0 < a < S1 < S 2 < b and also
S n +1 = Sn ⋅ S n −1 , n > 2 ………. (i)
Here S n > 0 , ∀ n ≥ 1 and a < S1 < b
Let for some k > 2
a < Sk < b
then a 2 < a Sk < Sk Sk −1 = ( Sk +1 )2 < b2 Q Sn +1 = Sn S n−1
i.e. a 2 < Sk2+1 < b2
⇒ a < S k +1 < b
⇒ a < Sn < b ∀ n ∈ ¥
S a
Q n >
Sn +1 b
S a
∴ n +1 > +1
Sn +1 b
Sequences and Series - 12 -
S n + S n+1 a+b
⇒ >
S n +1 b
S + S n+1 a+b
⇒ n > S n +1 is replace by S n ∴ S n < S n+1
Sn b
And Sn2+1 − Sn2 = Sn ⋅ Sn−1 − Sn2 Q Sn +1 = Sn S n−1
= Sn ( Sn−1 − Sn )
Sn
⇒ S n+1 − Sn = S n−1 − S n
S n + S n+1
b
< S n−1 − S n
a+b
b
⇒ S n+1 − Sn < Sn − S n−1 Q S n−1 − S n = S n − S n−1
a+b
2
b
< S n−1 − S n−2
a+b
3
b
< S n − 2 − S n −3
a+b
………………………
………………………
………………………
n −1
b
< (b − a )
a+b
b
Take r = <1
a+b
Then for n > m we have
Sn − Sm = Sn − Sn −1 + Sn −1 − Sn −2 + .............. + Sm+1 − Sm
≤ Sn − Sn−1 + Sn−1 − Sn−2 + .............. + Sm+1 − Sm
< ( r n −2 + r n −3 + ............... + r m−1 ) (b − a )
=ε
This implies that {Sn } is a Cauchy sequence, therefore it is convergent.
Example
Let {tn } be defined by
1 1 1
tn = 1 + + + ............... +
2 3 n
For m, n ∈ ¥ , n > m we have
1 1 1
tn − tm = + + ............. +
m +1 m + 2 n
1 m
> ( n − m) = 1 −
n n
In particular if n = 2m then
1
tn − tm >
2
This implies that {tn } is not a Cauchy sequence therefore it is divergent.
7⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅8
Sequences and Series - 13 -
Note:
(i) A bounded sequence has unique limit inferior and superior
(ii) Let {Sn } contains all the rational numbers, then every real number is a
subsequencial limit then limit superior of S n is + ∞ and limit inferior of S n is −∞
1
(iii) Let {S n } = (−1)n 1 +
n
then limit superior of S n is 1 and limit inferior of S n is −1 .
(iv) Let U k = inf {Sn : n ≥ k }
1 1 1
= inf 1 + cos kπ , 1 + cos( k + 1)π , 1 + cos(k + 2)π ,................
k k +1 k +2
1
1 + k cos kπ if k is odd
=
1 + 1 cos(k + 1)π if k is even
k + 1
⇒ lim ( inf Sn ) = lim U k = −1
n→∞ n→∞
Also Vk = sup{Sn : n ≥ k }
1
k + 1 cos(k + 1)π
1 + if k is odd
=
1 + 1 cos kπ if k is even
k
⇒ lim ( inf Sn ) = lim Vk = 1
n→∞ n→∞
ï⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅ð
Sequences and Series - 15 -
Theorem
If {Sn } is a convergent sequence then
lim S n = lim ( inf S n ) = lim ( sup S n )
n→∞ n→∞ n→∞
Proof
Let lim S n = s then for a real number ε > 0 , ∃ a positive integer n0 such that
n→∞
We can have the same result for limit inferior of {Sn } by taking
U k = inf {Sn : n ≥ k }
ï⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅ð
Sequences and Series - 16 -
Infinite Series
∞
Given a sequence {an } , we use the notation ∑a
i =1
n or simply ∑an to denotes the
If the sequence {Sn } converges to s, we say that the series converges and write
∞
∑a
n=1
n = s , the number s is called the sum of the series but it should be clearly
understood that the ‘s’ is the limit of the sequence of sums and is not obtained simply
by addition.
If the sequence {Sn } diverges then the series is said to be diverge.
Note:
The behaviors of the series remain unchanged by addition or deletion of the certain
terms
Theorem
∞
If ∑a
n=1
n converges then lim an = 0 .
n→∞
Proof
Let S n = a1 + a2 + a3 + .......... + an
Take lim S n = s = ∑ an
n→∞
Since an = Sn − S n −1
Therefore lim an = lim ( S n − S n−1 )
n→∞ n→∞
= lim S n − lim S n−1
n→∞ n→∞
=s−s=0
Note:
The converse of the above theorem is false
Example
∞
1
Consider the series ∑n.
n=1
1 1 1
We know that the sequence {Sn } where S n = 1 + + + ............. + is divergent
2 3 n
∞
1
therefore ∑n
n=1
is divergent series, although lim an = 0 .
n→∞
∑a
i = m +1
i <ε ∀ n > m > n0
Proof
Let S n = a1 + a2 + a3 + ............. + an
then {Sn } is convergent if and only if for ε > 0 ∃ a positive integer n0 such that
Sequences and Series - 17 -
Example
∞
1
If x < 1 then ∑x
n= 0
n
=
1− x
∞
And if x ≥ 1 then ∑x
n =0
n
is divergent.
Theorem
Let ∑ an be an infinite series of non-negative terms and let {Sn } be a sequence of
its partial sums then ∑ an is convergent if {Sn } is bounded and it diverges if {Sn } is
unbounded.
Proof
Since an ≥ 0 ∀ n ≥ 0
S n = S n−1 + an > S n−1 ∀ n≥0
therefore the sequence {Sn } is monotonic increasing and hence it is converges if
{Sn } is bounded and it will diverge if it is unbounded.
Hence we conclude that ∑a n is convergent if {Sn } is bounded and it divergent if
{Sn } is unbounded.
Theorem (Comparison Test)
Suppose ∑ an and ∑ bn are infinite series such that an > 0 , bn > 0 ∀ n . Also
suppose that for a fixed positive number λ and positive integer k , an < λ bn ∀ n ≥ k
Then ∑a n converges if ∑b n is converges and ∑b n is diverges if ∑a n is diverges.
Proof
Suppose ∑b is convergent and
n
from (i)
n n
∑ ⇒
i =m +1
ai < λ ∑ b <ε
i = m +1
i , n > m > n0
⇒ ∑a n is convergent.
Now suppose ∑ a is divergent then {Sn } is unbounded.
n
∑ b >λβ
i = m +1
i , n>m
from (i)
n
1 n
⇒ ∑ bi > ∑ ai > β , n>m
i =m +1 λ i =m+1
⇒ ∑ bn is convergent.
Sequences and Series - 18 -
Example
1
We know that ∑n is divergent and
n≥ n ∀ n ≥1
1 1
⇒ ≤
n n
1 1
⇒ ∑
n
is divergent as ∑n is divergent.
Example
1
The series ∑n α
is convergent if α > 1 and diverges if α ≤ 1 .
1 1 1
Let Sn = 1 + + + .................. +
2α 3α nα
If α > 1 then
1 1
Sn < S2n and <
nα (n − 1)α
1 1 1 1
Now S 2 n = 1 + α + α + α ............ +
2 3 4 (2n)α
1 1 1 1 1 1 1
= 1 + α + α + ............ + + + + + +
(2n − 1)α 2α 4α 6α (2n)α
............
3 5
1 1 1 1 1 1 1
= 1 + α + α + ............ + α
+ α 1 + α + α + ............ + α
3 5 (2n − 1) 2 2 3 ( n)
1 1 1 1
< 1 + α + α + ............ + α
+ Sn
2 4 (2n − 2) 2α
replacing 3 by 2, 5 by 4 and so on.
1 1 1 1
=1 + + + + +
2α 2α (n − 1)α 2α
1 ............ Sn
1 1 1 1
=1 + α Sn −1 + α S n =1 + α S 2 n + α S2 n Q Sn −1 < S n < S 2 n
2 2 2 2
2
=1 + α S 2 n
2
1
⇒ S 2 n < 1 + α −1 S 2 n
2
1 2α −1 − 1 2α −1
⇒ 1 − α −1 S 2 n < 1 ⇒ α −1 S 2 n < 1 ⇒ S 2 n < α −1
2 2 2 −1
2α −1
i.e. S n < S 2 n < α −1
2 −1
1
⇒ {Sn } is bounded and also monotonic. Hence we conclude that ∑ α is
n
convergent when α > 1 .
If α ≤ 1 then
nα ≤ n ∀ n ≥ 1
1 1
⇒ α ≥ ∀ n ≥1
n n
1 1
Q ∑ is divergent therefore ∑ α is divergent when α ≤ 1.
n n
Sequences and Series - 19 -
Theorem
an
Let an > 0 , bn > 0 and lim
n→∞ b
= λ ≠ 0 then the series ∑a n and ∑b n behave alike.
n
Proof
an
Since lim =λ
n→∞ b
n
an
⇒ − λ < ε ∀ n ≥ n0 .
bn
λ
Use ε =
2
a λ
⇒ n −λ < ∀ n ≥ n0 .
bn 2
λ a λ
⇒ λ− < n <λ+
2 bn 2
λ an 3λ
⇒ < <
2 bn 2
then we got
3λ 2
an < bn and bn < an
2 λ
Hence by comparison test we conclude that ∑a n and ∑b n converge or diverge
together.
Example
1 x
To check ∑ n sin n
2
diverges or converges consider
1 x 1
an = sin 2 and take bn = 3
n n n
an x
then = n 2 sin 2
bn n
2
x 2 x
sin sin
= n = x2 n
1 x
n2 n
Applying limit as n → ∞
2 2
x x
sin sin
an 2 n 2 n = x 2 (1) = x 2
lim = lim x = x lim
n→∞ b n→∞ x n→∞ x
n
n n
⇒ ∑ an and ∑ bn have the similar behavior ∀ finite values of x except x = 0.
1
Since ∑n 3
is convergent series therefore the given series is also convergent for
finite values of x except x = 0.
ï⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅ð
Sequences and Series - 20 -
Example
1
Consider the series ∑n p
1
If p ≤ 0 then lim ≠0
n→∞ n p
(2 ) k =0 2
∞ ∞ k
1 1
=∑ = ∑ ( p −1)
k =0 2( p −1) k k =0 2
∞
= ∑2
k =0
(1− p ) k
1− p
Now 2 < 1 iff 1 − p < 0 i.e. when p > 1
Sequences and Series - 21 -
And the result follows by comparing this series with the geometric series having
common ratio less than one.
The series diverges when 21− p = 1 ( i.e. when p = 1 )
The series is also divergent if 0 < p < 1.
Example
∞
∑ n (ln n)
1
If p > 1 , p
converges and
n= 2
1 1
⇒ a2n = ⇒ 2 n a2n =
( ) ( n ln 2 )
p p
2 n ln 2 n
⇒ we have the series
1 1 1
∑ 2n a2n = ∑ (n ln 2) p = ( ln 2 ) p ∑ n p
which converges when p > 1 and diverges when p ≤ 1 .
Example
1
Consider ∑ ln n
1
Since {ln n} is increasing there decreases.
ln n
And we can apply the condensation test to check the behavior of the series
1 1
Q an = ∴ a2n =
ln n ln 2 n
2n 2n
so 2 a2n =
n
⇒ 2 a2n =
n
ln 2n n ln 2
n
2 1
since > ∀ n ≥1
n n
1
and ∑ is diverges therefore the given series is also diverges.
n
ï⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅⋅ð
Sequences and Series - 22 -
Alternating Series
A series in which successive terms have opposite signs is called an alternating series.
(−1)n +1 1 1 1
e.g. ∑ = 1 − + − + ............... is an alternating series.
n 2 3 4
Theorem (Alternating Series Test or Leibniz Test)
Let {an } be a decreasing sequence of positive numbers such that lim an = 0 then the
n→∞
∞
alternating series ∑ (−1)
n=1
n+1
an = a1 − a2 + a3 − a4 + ................ converges.
Proof
Looking at the odd numbered partial sums of this series we find that
S 2 n +1 = (a1 − a2 ) + (a3 − a4 ) + (a5 − a6 ) + ........... + (a2 n−1 − a2 n ) + a2 n+1
Since {an } is decreasing therefore all the terms in the parenthesis are non-negative
⇒ S 2 n +1 > 0 ∀ n
Moreover
S 2 n +3 = S 2 n+1 − a2 n+2 + a2 n+3
= S2 n +1 − ( a2 n +2 − a2 n+3 )
Since a2 n+ 2 − a2 n +3 ≥ 0 therefore S 2 n +3 ≤ S 2 n +1
Hence the sequence of odd numbered partial sum is decreasing and is bounded below
by zero. (as it has +ive terms)
It is therefore convergent.
Thus S 2 n+1 converges to some limit l (say).
Now consider the even numbered partial sum. We find that
S 2 n +2 = S2 n+1 − a2 n+ 2
and
lim S 2 n+ 2 = lim ( S 2 n+1 − a2 n +2 )
n→∞ n→∞
= lim S 2 n+1 − lim a2 n+2
n→∞ n→∞
=l −0 =l Q lim an = 0
n→∞
so that the even partial sum is also convergent to l .
⇒ both sequences of odd and even partial sums converge to the same limit.
Hence we conclude that the corresponding series is convergent.
Absolute Convergence
∑ an is said to converge absolutely if ∑a n converges.
Theorem
An absolutely convergent series is convergent.
Proof:
If ∑ an is convergent then for a real number ε > 0 , ∃ a positive integer n0 such that
n n
∑a
i = m +1
i < ∑
i = m +1
ai < ε ∀ n, m > n0
⇒ ∑ a converges absolutely.
n
Now let p > 1 then we can find a number ε1 > 0 such that p − ε1 > 1 .
1
⇒ an n
> p +ε > 1
⇒ an > 1 for infinitely many values of n.
⇒ lim an ≠ 0
n→∞
⇒ ∑a n is divergent.
Note:
The above test give no information when p = 1 .
1 1
e.g. Consider the series ∑ and ∑ 2 .
n n
1 1
For each of these series p = 1 , but ∑ is divergent and ∑n 2
is convergent.
n
Theorem (Ratio Test)
The series ∑ an
an+1
(i) Converges if lim Sup <1
n→∞ an
an +1
(ii) Diverges if > 1 for n ≥ n0 , where n0 is some fixed integer.
an
Proof
If (i) holds we can find β < 1 and integer N such that
an +1
< β for n ≥ N
an
In particular
a N +1
< β
aN
⇒ aN +1 < β aN
⇒ aN +2 < β aN +1 < β 2 aN
⇒ a N +3 < β 3 a N
…………………….
…………………….
…………………….
⇒ a N + p < β p aN
Sequences and Series - 24 -
⇒ an < β n − N aN we put N + p = n .
i.e. an < aN β − N β n for n ≥ N .
Q ∑β n
is convergent because it is geometric series with common ration < 1 .
Therefore ∑a n is convergent (by comparison test)
Now if
an+1 ≥ an for n ≥ n0
then lim an ≠ 0
n→∞
⇒ ∑a n is divergent.
Note
an +1
The knowledge = 1 implies nothing about the convergent or divergent of series.
an
Example
−n
n n
n+1
Also ( an ) n = −
n + 1 n + 1
−1 −1
n +1 n n +1 n +1
n −n
= 1 − = 1 −
n n + 1 n n
−1
1 1
−n
= 1 + 1 − 1 +
n n
−1
1 1
−n
lim an = lim 1 + 1 − 1 +
n→∞ n→∞
n n
−1
1 1 − n
= lim 1 + lim 1 − 1 +
n→∞
n n→∞ n
−1 −1
−1 −1 1 e − 1 e
= 1 ⋅ 1 − e = 1 − = = >1
e e e − 1
⇒ the series is divergent.
Theorem (Dirichlet)
Suppose that {Sn } , S n = a1 + a2 + a3 + ............. + an is bounded. Let { bn } be positive
term decreasing sequence such that lim bn = 0 , then
n→∞
∑a n bn is convergent.
Proof
Q {Sn } is bounded
∴ ∃ a positive number λ such that
Sn < λ ∀ n ≥ 1.
Then ai bi = ( Si − Si −1 ) bi for i ≥ 2
= Si bi − Si−1 bi
= Si bi − Si−1 bi + Si bi +1 − Si bi +1
Sequences and Series - 25 -
= Si ( bi − bi+1 ) − Si −1 bi + Si bi +1
n n
⇒ ∑
i = m +1
ai bi = ∑ S (b − b ) − ( S
i = m +1
i i i +1 m bm+1 − S n bn +1 )
Q { bn } is decreasing
n n
∴ ∑ab
i = m +1
i i = ∑ S (b − b ) − S
i = m+1
i i i +1 m bm+1 + Sn bn+1
n
< ∑ { S (b − b )} +
i = m +1
i i i +1 S m bm+1 + S n bn +1
n
< ∑ {λ (b − b )} + λ b
i = m +1
i i +1 m +1 + λ bn+1 Q Si < λ
n
= λ ∑ ( bi − bi+1 ) + bm+1 + bn +1
i =m+1
= λ ( ( bm+1 − bn+1 ) + bm+1 + bn +1 ) = 2λ ( bm+1 )
n
⇒ ∑ab
i = m +1
i i <ε where ε = 2λ ( bm+1 ) a certain number
Theorem
Suppose that ∑a n is convergent and that { bn } is monotonic convergent sequence
then ∑a n bn is also convergent.
Proof
Suppose { bn } is decreasing and it converges to b .
Put cn = bn − b
⇒ cn ≥ 0 and lim cn = 0
n→∞
Q ∑a n is convergent
∴ {Sn } , S n = a1 + a2 + a3 + ................. + an is convergent
⇒ It is bounded
⇒ ∑ an cn is bounded.
Q an bn = an cn + an b and ∑a n cn and ∑a n b are convergent.
∴ ∑a n bn is convergent.
Now if { bn } is increasing and converges to b then we shall put cn = b − bn .
Example
1
∑ (n ln n) α
is convergent if α > 1 and divergent if α ≤ 1.
2n 1
= =
2nα nα ( ln 2 ) 2nα −n nα ( ln 2 )
α α
Sequences and Series - 26 -
(α −1) n
1
⋅ α
1 2
=
( ln 2 )
α
n
(α −1) n
1 1
Since ∑ α is convergent when α > 1 and is decreasing for α > 1 and it
n 2
converges to 0. Therefore ∑ bn is convergent
⇒∑ a is also convergent.
n
Example
1
To check ∑n α
ln n
is convergent or divergent.
1
We have an = α
n ln n
2n 2n
Take bn = 2 a2n n
= = nα
(2 n )α (ln 2 n ) 2 (n ln 2)
(α −1) n
1
1 2(1−α ) n 1 2
= ⋅ = ⋅
ln 2 n ln 2 n
1 1 n (α −1)
Q ∑ is divergent although is decreasing, tending to zero for α > 1
n 2
∑ b is divergent.
therefore n
⇒ ∑ a is divergent.
n